Effect-directed analysis supporting monitoring of aquatic environments--An in-depth overview - Brack, Werner; Ait-Aissa, Selim; Burgess, Robert M; Busch, Wibke; Creusot, Nicolas; Di Paolo, Carolina; Escher, Beate I; Mark Hewitt, L; Hilscherova, Klara; Hollender, Juliane; Hollert, Henner; Jonker, Willem; et al. (The Science of the total environment, 2016)
Aquatic environments are often contaminated with complex mixtures of chemicals that may pose a risk to ecosystems and human health. This contamination cannot be addressed with target analysis alone but tools are required to reduce this complexity and identify those chemicals that might cause adverse effects. Effect-directed analysis (EDA) is designed to meet this challenge and faces increasing interest in water and sediment quality monitoring. Thus, the present paper summarizes current experience with the EDA approach and the tools required, and provides practical advice on their application. The paper highlights the need for proper problem formulation and gives general advice for study design. As the EDA approach is directed by toxicity, basic principles for the selection of bioassays are given as well as a comprehensive compilation of appropriate assays, including their strengths and weaknesses. A specific focus is given to strategies for sampling, extraction and bioassay dosing since they strongly impact prioritization of toxicants in EDA. Reduction of sample complexity mainly relies on fractionation procedures, which are discussed in this paper, including quality assurance and quality control. Automated combinations of fractionation, biotesting and chemical analysis using so-called hyphenated tools can enhance the throughput and might reduce the risk of artifacts in laboratory work. The key to determining the chemical structures causing effects is analytical toxicant identification. The latest approaches, tools, software and databases for target-, suspect and non-target screening as well as unknown identification are discussed together with analytical and toxicological confirmation approaches. A better understanding of optimal use and combination of EDA tools will help to design efficient and successful toxicant identification studies in the context of quality monitoring in multiply stressed environments.
Keywords: Dosing; Bioassay; Enrichment; Biological Assay; nebezpečné látky; Risk Assessment; monitorování životního prostředí; Environmental Monitoring; Hazardous Substances; Ecosystem; hodnocení rizik; Fractionation; biotest; ekosystém; Non-target analysis; Toxicant identification